MORPHOMETRY OF THE SHELL OF DONAX DENTICULATUS AND DONAX STRIATUS OF TWO BEACHES OF CUBA ORIENTAL - Ocaña, Frank A.; Fernández, Alejandro (Revista Ciencias Marinas y Costeras, 2011)
Studies have been conducted on the morphology and ecology of Donax striatus and D. denticulatus in the Caribbean beaches. However, no investigation has been focused on their morphometry as to apply this information to determine a guideline for the exploitation of this resource. The objective of this paper is to quantify the relationships between morphometric variables and verify whether the Shell Shape Stabilization Indicator (IEF, Spanish acronym) is useful to determine the minimum size of catch for the two species. D. striatus is larger than D. denticulatus. In all cases, correlation between the morphometric variables is highly significant. In D. Striatus, shell shape stabilization is visible to occur at 15.48 mm in length; however, for D. denticulatus an inflexion point is not easily observed in the curves of the ratios between the morphometric measures. Results are not conclusive to propose the use of IEF as a guideline for fishery of Donax species. The minimum size of catch of D. striatus and D. denticulatus suggested should be established at 20 mm to allow individuals to reproduce at least once during their life cycle.